Work From Home on Employee Performance: Mediation Role by Work Life Balance - Muhammad Hafiz (Human Resource Management Studies, 2022)
The purpose of this research is to (1) identify and analyze the effect of work from home on employee performance (2) determine and analyze the effect of work from home on work life balance (3) identify and analyze the effect of work life balance on employee performance (4) identify and analyze the effect of work from home on employee performance with work life balance as a mediating variable at Bank Mandiri KCP Payakumbuh. The population in this study were employees of Bank Mandiri KCP Payakumbuh totaling 33 employees. The sampling technique used total sampling where the number of samples was the same as the population of 33 people. This data collection uses a questionnaire with a Likert scale and the analytical technique used is the Structural Equation Model with the help of SmartPLS 3.0. The results of this study indicate that: (1) work from home has a positive and insignificant effect on employee performance at Bank Mandiri KCP Payakumbuh (2) work from home has a positive and significant effect on work life balance at Bank Mandiri KCP Payakumbuh (3) work life balance positive and significant effect on employee performance at Bank Mandiri KCP Payakumbuh (4) work from home has a positive and significant effect on employee performance with work life balance as a mediating variable at Bank Mandiri KCP Payakumbuh.